2017
DOI: 10.3171/2016.5.jns16388
|View full text |Cite
|
Sign up to set email alerts
|

A novel miniature robotic device for frameless implantation of depth electrodes in refractory epilepsy

Abstract: OBJECTIVE The authors' group recently published a novel technique for a navigation-guided frameless stereotactic approach for the placement of depth electrodes in epilepsy patients. To improve the accuracy of the trajectory and enhance the procedural workflow, the authors implemented the iSys1 miniature robotic device in the present study into this routine. METHODS As a first step, a preclinical phantom study was performed using a human skull model, and the accuracy and timing between 5 electrodes implanted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 18 publications
(19 reference statements)
1
50
0
2
Order By: Relevance
“…The frameless systems included in the analysis include the Vertek arm (Medtronic), Varioguide (BrainLab), Navigus tool (Medtronic), and the Guide Frame‐DT (Medtronic) . A single study compared the use of the iSYS1 robotic trajectory guidance system for the insertion of 93 electrodes in 16 patients with a historical cohort using the Vertek arm frameless technique . The number of patients and baseline characteristics of the historical cohort was not specified.…”
Section: Discussionmentioning
confidence: 99%
“…The frameless systems included in the analysis include the Vertek arm (Medtronic), Varioguide (BrainLab), Navigus tool (Medtronic), and the Guide Frame‐DT (Medtronic) . A single study compared the use of the iSYS1 robotic trajectory guidance system for the insertion of 93 electrodes in 16 patients with a historical cohort using the Vertek arm frameless technique . The number of patients and baseline characteristics of the historical cohort was not specified.…”
Section: Discussionmentioning
confidence: 99%
“…Dorfer et al 10 reported a mean entry point LE of 1.3 mm (range 0.1-3.4 mm) from 93 electrodes implanted with optical tracking registration and an iSYS1 robot. For the subset of the most recent 31 electrode implantations with optimized hardware, they reported a mean entry point LE (± SD) of 1.18 ± 0.5 mm.…”
Section: Accuracy In Clinical Studies For Seegmentioning
confidence: 99%
“…The analysis was carried out in similar conditions, adding some hardware for SEEG procedure optimization. 10 Von Langsdorff et al 27 reported a mean accuracy (± SD) of 0.44 ± 0.23 mm, coupling the Fisher frame and Neuromate in a 21-trajectory study. Nevertheless, details about the planning data sets and the coregistration method were not provided.…”
Section: Accuracy In Phantom Studies For Robotic Brain Surgerymentioning
confidence: 99%
“…Frameless techniques include both stereotactic robotic techniques 9) and frameless neuronavigation techniques with or without stereotactic techniques. 6,10,11) …”
Section: Introductionmentioning
confidence: 99%
“…Frame-based methods and stereotactic robotic guidance methods are certainly accurate, but carry several drawbacks 10,12) including the need for highly expensive stereotactic robotic equipment or restricted access to the surgical field in frame-based methods. As a result, these methods are not commonly used, whereas neuronavigation systems are widely used in the neurosurgical field.…”
Section: Introductionmentioning
confidence: 99%